Studies in gelly-fungi Auriculariales - and S.D. NANAWARE, M.S. PATIL, B.D. KUNDALKAR (Indian Phytopathology, 2003)
The present paper describes nine new taxa (8 species and one variety) comprising of three genera viz. Achroomyces (6 spp. and one variety), Helicobasidium (one species) and Helicog/oea (one species) of the family Auriculariaceae. Two genera (Achroomyces and Helicog/oea) are recorded for the first time in India. All the taxa studied are lignicolous except one, which is mycoparasitic. All the new taxa proposed are purely based on morphological ground. The genus Achroomyces is dominant.